2007
DOI: 10.1007/s00442-007-0815-y
|View full text |Cite
|
Sign up to set email alerts
|

An isotopic method for testing the influence of leaf litter quality on carbon fluxes during decomposition

Abstract: During microbial breakdown of leaf litter a fraction of the C lost by the litter is not released to the atmosphere as CO(2) but remains in the soil as microbial byproducts. The amount of this fraction and the factors influencing its size are not yet clearly known. We performed a laboratory experiment to quantify the flow of C from decaying litter into the soil, by means of stable C isotopes, and tested its dependence on litter chemical properties. Three sets of (13)C-depleted leaf litter (Liquidambar styracifl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Thermogravimetric analysis (TGA, Fig. 1a) revealed opposing trends in the quantities of thermal labile (for example, polysaccharides), recalcitrant/refractory (for example, lipids) and inert/charred compounds in the soils 22 . Substantial fractions of labile compounds were present throughout the mofette, and while the ratio of labile to recalcitrant fractions was fairly stable at 1.4 ± 0.1 in the mofette, it decreased from 2.1 (0-5 cm) to 1.0 (>20 cm) in the reference.…”
Section: Resultsmentioning
confidence: 99%
“…Thermogravimetric analysis (TGA, Fig. 1a) revealed opposing trends in the quantities of thermal labile (for example, polysaccharides), recalcitrant/refractory (for example, lipids) and inert/charred compounds in the soils 22 . Substantial fractions of labile compounds were present throughout the mofette, and while the ratio of labile to recalcitrant fractions was fairly stable at 1.4 ± 0.1 in the mofette, it decreased from 2.1 (0-5 cm) to 1.0 (>20 cm) in the reference.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is a lack of knowledge about the relationship between biochemical and thermal stability (reviewed by Plante et al, 2009). A recent study demonstrated that thermogravimetry (TG) can easily estimate the decomposition potential of leaf litter in upland soils (Rubino et al, 2007). Based on these data, we conclude a relationship between litter composition and microbial CO 2 formation as the proportion of thermal labile compounds and CO 2 respiration rates decreased during an 8-month incubation period.…”
Section: Introductionmentioning
confidence: 72%
“…Approximately 5 mg of each dried and milled peat sample (in two replicates) was analyzed by thermogravimetry (Mettler Toledo, TGA/SDTA 851e, Switzerland) (TG) (Pope and Judd, 1977). The mass loss at increasing temperatures (10.2 • C min −1 ) was measured under a continuous flow of argon from 60 to 850 • C followed by a final combustion under oxygen at 850 • C (Rubino et al, 2007). Pyrolysis under anoxic conditions was done first to estimate the amount of thermal labile compounds.…”
Section: Analytical Techniquesmentioning
confidence: 99%
See 2 more Smart Citations